Influence of raw rice husk addition on structure and properties of concrete - Yuzer, Nabi; Cinar, Zekiye; Akoz, Fevziye; Biricik, Hasan; Gurkan, Yelda Yalcin; Kabay, Nihat; Kizilkanat, Ahmet B. (ELSEVIER SCI LTD, 2013)
When concrete is exposed to high temperatures, vapor pressure increases and the concrete may spall. In order to prevent this, polypropylene fibers are added to concrete. However, it is known that these fibers produce harmful gases at high temperatures that affect health. In this study, instead of polypropylene fibers, the usability of raw rice husk which is a by-product of paddy-rice dehusking was tested in normal strength concrete. Four concrete series were produced with a constant water/cement ratio and slump and exposed to high temperatures. Compressive strength, density, ultrasonic pulse velocity, thermal conductivity and water vapor diffusion resistance factor were investigated experimentally. FT-IR, SEM, XRD and BET analyses were also performed. Although the use of rice husk reduces mechanical strength, it provides benefits in other properties. Rice husk reduces vapor pressure within the concrete thus prevents spalling and releases less harmful gases than polypropylene fibers. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Raw rice husk; Concrete; Microstructure; High temperature; Adsorption; HIGH-PERFORMANCE CONCRETE; STRENGTH; PARAMETERS; AGGREGATE; HYDRATION; CEMENT; Construction & Building Technology; Engineering; Materials Science